PENGARUH BEBERAPA RASIO KEUANGAN TERHADAP HARGA SAHAM, STUDY EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (UNIKA Santo Thomas, 2010)
This study wants to analyze the inï¬‚uence of fundamental factors on stock prices listed manufacturing in Indonesia Stock Exchange with the observation period Z004 to 2006. Fundamental analysis is used to assess the feasibility of investing in the stock because it can generate the variables that determine stock prices in the ï¬tture. Valuation concept stocks with ï¬tndamental analysis will yield information about whether a particular stock worth buying or not feasible, based on the opportunity to generate returns. To perform this analysis, it would require the company's ï¬nancial data and other data related to the concept of stock valuation. One source of information that can be used is the company's ï¬nancial statements. Pniecahan study focused on the issue of corporate fundamental factors jointly inï¬‚uence the stock price companies manufacturing in Indonesia Stock Exchange and what factors aï¬‚ect the price of the most dominant share of manufacturing companies in Indonesia Stock Exchange. The study aimed to determine the influence of fundamental factors together (simultaneously) on stock prices of manufacturing companies in Indonesia Stock Exchange and to determine the factors that most inï¬‚uence the predominantly manufacturing companyâ€˜s stock price in the Indonesia Stock Exchange. The results showed that the six independent variables are return on equity (ROE), debt to equity ratio (DER), net book value (NVB), dividend payout ratio (DPR), dividend growth (GTH) and the expected rate of return (KS5) significantly inï¬‚uence the company's stock price is publicly traded on the Indonesia Stock Exchange with a coeï¬‚icient value of R-squared = 0.828758 and Adjusted R-squared = 0.821720 with 0.0000 signiï¬cance. These results indicate that all six variables are taken into consideration appropriate to analyze the stock prices of publicly traded companies in Indonesia Stock Exchange. The most dominant factor afï¬ecting the stock price of publicly traded companies in Indonesia Stock Exchange is the net book value (NBV) with keï¬sien value of 0.647716. The analysis of this study indicate that the parties - stakeholders should consider the variable return on equity (ROE), debt to equity ratio (DER), net book value (NVB), dividend payout ratio (DPR), dividend growth (GTH) and the expected beneï¬ts (KS5) in making decisions.